Neutrophils 2019
DOI: 10.5772/intechopen.81995
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptors as Regulators of Neutrophil Activity in Inflammatory Diseases

Abstract: Cannabinoids are compounds present in Cannabis sativa (phytocannabinoids), endogenously produced (endocannabinoids) or synthesized, that bind to G protein-coupled receptors named cannabinoid receptors B1 and B2. They were first described as psychotropic compounds; however, cannabinoids are also potent immunoregulatory agents. Cannabinoids can modulate neutrophil activity in sterile and infectious inflammatory diseases. Concerning sterile inflammatory diseases as arthritis, ischemic diseases, and colitis, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Cannabinoids modulate several aspects of PMN biology 76 . However, the role of the cannabinoid system on PMN migration is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids modulate several aspects of PMN biology 76 . However, the role of the cannabinoid system on PMN migration is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the cannabinoid system on PMN migration is controversial. Some studies showed that CB activation did not affect PMN migration, whereas other authors demonstrated that CB agonists induced migration of PMNs toward inflammatory stimuli 21,76,77 . Two membrane‐bound glycoproteins (i.e., CD66b and CD62L) regulating their adhesive property are involved in neutrophil migration and activation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Eligible patients were those diagnosed with plaque psoriasis for at least 6 months with lesions affecting at least 10% of total body surface area. The severity of psoriasis was assessed using the Psoriasis Area and Severity Index (PASI) score (median 17; range [13][14][15][16][17][18][19][20][21]. None of the patients or healthy subjects received topical, injectable or oral medications during the 4 weeks before the study.…”
Section: Effects Of Cbd On Apoptosis In Uvb-irradiated Keratinocytesmentioning
confidence: 99%
“…Options for integrative biomedicine treatments combining UV therapy with antiinflammatory compounds seem attractive and aim to eliminate the negative and intensify the positive effects of UV irradiation. Cannabidiol (CBD), a phytocannabinoid that not only has anti-inflammatory properties but also is a powerful antioxidant [15][16][17], seems to be a potentially promising compound for such therapy. CBD has positive effects on psoriatic skin cells [17][18][19] and can protect healthy cells from the negative effects of UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of endocannabinoid receptors on immune cells results in a decrease in proinflammatory cytokine release 14 , 15 and reduces the neutrophil and macrophage recruitment. 16 Multicellular damage caused by proinflammatory and pro-oxidative mediators leads to multiple organ dysfunction, worsening of the patient's general medical condition, and finally, death. Considering the role of endocannabinoids, we hypothesized that they could be early predictors of severe events in sepsis.…”
Section: Introductionmentioning
confidence: 99%